The Role of the Five Loyalties Philosophy in Creating Business Sustainability for Small and Medium Enterprises in Bali - Normal, I Nyoman; Wiksuana, I Gusti Bagus; Candraningrat, Ica Rika; Baskara, I Gde Kajeng (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The number of Small and Medium Enterprises (SMEs) in Bali declined by 18.42% in 2023, threatening business sustainability, partly due to limited managerial capabilities. This study examines the effect of financial capability on SME business sustainability, with financial performance as a mediator and the Panca Satya (Five Loyalties) philosophy as a moderator. Data were collected from 177 SMEs using proportional stratified random sampling and a questionnaire. The hypotheses were tested using partial least squares structural equation modelling (PLS-SEM). The results show that financial capability positively affects both financial performance and business sustainability. Financial performance partially mediates this relationship. While the Panca Satya philosophy positively predicts business sustainability, it does not significantly moderate the relationship between financial capability and business sustainability. This study contributes to the literature by positioning Panca Satya as an indigenous cultural resource that supports sustainable entrepreneurship and broadens the application of local wisdom in sustainability research.
Keywords: panca satya philosophy; business sustainability; small and medium enterprises (SMEs)